Aplikasi Berbagai Jenis Plant Growth Promoting Rhizobacteria (PGPR) dalam Meningkatkan Pertumbuhan dan Hasil Cabai Merah - Budiyati Ichwan; Trias Novita; Eliyanti Eliyanti; Ella Masita (Jurnal Media Pertanian, 2021)
This study aims to examine the effect of PGPR in increasing the growth and yield of red chilies, and to find the type of PGPR that gives the best growth and yield in red chilies. The research was conducted at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, 35 above sea level. The study used a randomized block design with one factor, namely various types of PGPR: without PGPR; PGPR1 (containing Trichoderma sp., Bacillus sp., Pseudomonas sp., 11 essential macro and microelements, as well as natural amino acids); PGPR 2 (containing Pseudomonas fluorescent, Trichoderma sp., Aspergillus niger, Azobacter sp., Azospirilium sp., And Rhizobium sp.); PGPR 3 (containing Trichoderma sp., Pseudomonas sp., And Rhizobium sp.); and PGPR 4 (containing Azosbacteria sp, Aspergillus niger, and Trichoderma harzianum). Each treatment was repeated five times. The results showed that the application of PGPR was able to increase plant growth and yield of red chilies in the form of plant height (2.12% - 9.69%), the total number of branches (5.25% -54.96%), number of fruits (13,55% -51.40%) and fruit weight (54.19% -116.35%). The quality of crop yields has also improved with the application of PGPR. PGPR which contains Pseudomonas fluorescent, Trichoderma sp, Aspergillus niger, Azobacter sp, Azospirilium sp, and Rhizobium sp. is PGPR that provides the best growth and yield of red chilies